2006
DOI: 10.1124/mol.106.028563
|View full text |Cite
|
Sign up to set email alerts
|

Repression of HumanGSTA1by Interleukin-1β Is Mediated by Variant Hepatic Nuclear Factor-1C

Abstract: Down-regulation of glutathione transferase A1 (GSTA1) expression has profound implications in cytoprotection against toxic by-products of lipid peroxidation produced during inflammation. We investigated the role of hepatic nuclear factor 1 (HNF-1) in repression of human GSTA1 expression by interleukin (IL)-1␤ in Caco-2 cells. In luciferase reporter assays, overexpression of HNF-1␣ increased GSTA1 transcriptional activity via an HNF-1 response element (HRE) in the proximal promoter. In addition, constitutive mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
(41 reference statements)
1
4
0
Order By: Relevance
“…Our results are in agreement with other observations indicating that NO-Derived Oxidants inhibit GST expression (Wong et al 2001). The transcriptional suppression of GST by IL-1β is known to be mediated by hepatic nuclear factor [Ng et al, 2007]. Furthermore, our findings strongly suggest that GST inactivation after IL-1β addition could be attributed, in part, to NO generation.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with other observations indicating that NO-Derived Oxidants inhibit GST expression (Wong et al 2001). The transcriptional suppression of GST by IL-1β is known to be mediated by hepatic nuclear factor [Ng et al, 2007]. Furthermore, our findings strongly suggest that GST inactivation after IL-1β addition could be attributed, in part, to NO generation.…”
Section: Discussionsupporting
confidence: 93%
“…More relevant to our study is the marked up-regulation of GSTA1 expression during differentiation of postconfluent Caco-2 cells [14], [30], [31]. This finding supports the results of a study by Scharmach et al, 2009 that demonstrated marked induction of GSTA1, GSTA2 and to a lesser extent GSTA3 in association with Caco-2 cell differentiation whereas constant high expression was observed for GSTP1 and GSTO1, marginal expression for GSTA4, GSTT2 and GSTZ1 and no expression of GSTM5 and GSTT1 [30].…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, busulfan‐induced steatosis might occur only in patients with high hepatic GSTA1 expression, as the one found in the female patient whose liver tumor was used for the isolation of the HepaRG cell line [19]. Notably, various factors can significantly modulate GSTA1 expression including genetic polymorphism [64], hormones [65], and cytokines [66]. Whether high GSTA1 expression is uncommon in the general population would require further investigations.…”
Section: Discussionmentioning
confidence: 99%